Even Intensity and Implementation of Fuzzy Intrinsic Edge-Magic Graphs - Kaliraja, M.; Sasikala, M. (Communications in Mathematics and Applications, 2024)
A graph labelling is an assignment of integers to the vertices or edges, or both under certain restrictions. A fuzzy graph \(G\) is said to be intrinsic edge-magic if it satisfies the intrinsic edge-magic labelling with intrinsic constant \(λ _c=σ (v_i) +μ (v_iv_j)+σ (v_j)\), for all \(v_i, v_j V\). In this article, we introduce the even intensity of intrinsic edge magic graph and the application of fuzzy intrinsic edge magic graph is illustrated with suitable example.